1424. Factors Associated with Failure to Clear Candidemia Infection: Surveillance Data from Eight States, 2017. (31st December 2020) - Oh, David H; Seagle, Emma; Lockhart, Shawn R; Nadle, Joelle; Barter, Devra; Johnston, Helen; Farley, Monica M; Revis, Andrew; Pattee, Brittany; Phipps, Erin C; Tesini, Brenda L; Zhang, Alexia Y; et al.
Abstract: Background: Candidemia is a bloodstream infection commonly associated with high morbidity and mortality. Failure to clear candidemia can lengthen hospitalization and treatment. Factors associated with candidemia clearance are unknown. Methods: We analyzed 2017 candidemia surveillance data from the Centers for Disease Control and Prevention's Emerging Infections Program. Data from eight sites (counties in California, Colorado, Georgia, Minnesota, New Mexico, New York, Oregon, and Tennessee) were included. Clearance was defined as having a blood culture negative for Candida ≤30 days after initial culture date (ICD). Cases with unknown clearance, unknown survival outcome, or death ≤30 days of ICD were excluded. Demographic and clinical factors associated with clearance were assessed with bivariate analysis using chi-square tests and multivariable logistic regression to calculate adjusted odds ratios (aOR) using backward selection (p-value< 0.10). Results: Of 1, 024 candidemia cases, 737 were included and 582 (79%) demonstrated clearance, of which 79% had evidence of clearance ≤5 days after ICD. In bivariate analysis, clearance was associated with central venous catheter (CVC) ≤2 days before ICD, CVC removal ≤7 days after ICD, and systemic antifungal medication within 14 days before ICD. Clearance was inversely associated with black race and admission from another hospital. In multivariable analysis, only race and admission from another hospital were significant predictors; age, sex, and CVC presence and subsequent removal were also retained for their clinical relevance. In the final model, clearance was less likely among black patients (aOR 0.51, 95% confidence interval [CI] 0.29-0.91) and those admitted from another hospital (aOR 0.28, 95% CI 0.11-0.75). Table 1. Bivariate associations for select variables between individuals with documented candidemia clearance and those without documented clearance in eight Emerging Infections Program surveillance sites, 2017 Conclusion: We found failure to clear candidemia infection to be associated with black race and prior hospital exposure, but not other factors previously shown to be associated (e.g., comorbidities, CVC presence). These associations could reflect illness severity, access to care, or other obstacles to effective treatment. Additional research is needed to investigate these associations further and identify other factors (e.g., treatment type and timing) to improve outcomes. Disclosures: All Authors : No reported disclosures